2017
DOI: 10.1016/j.jagp.2017.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Steeper Slope of Age-Related Changes in White Matter Microstructure and Processing Speed in Bipolar Disorder

Abstract: Objectives Bipolar disorder (BD) is associated with compromised white matter (WM) integrity and deficits in processing speed (PS). However, few studies have investigated age relationships with WM structure and cognition to understand possible changes in brain health over the lifespan. This investigation explored whether BD and healthy comparison (HC) participants exhibited differential age-related associations with WM and cognition, which may be suggestive of accelerated brain and cognitive aging. Design Cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…This interpretation is consistent with the literature that comprises reports of reduced FA in the CST in individuals with or at risk for BD and in individuals with ADHD . The CST is a major motor pathway, and its microstructure has been positively associated with processing speed . Thus, altered WM microstructure in the CST might contribute to both reduced processing speed in BD.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This interpretation is consistent with the literature that comprises reports of reduced FA in the CST in individuals with or at risk for BD and in individuals with ADHD . The CST is a major motor pathway, and its microstructure has been positively associated with processing speed . Thus, altered WM microstructure in the CST might contribute to both reduced processing speed in BD.…”
Section: Discussionsupporting
confidence: 91%
“…44 The CST is a major motor pathway, and its microstructure has been positively associated with processing speed. 45 Thus, altered WM microstructure in the CST might contribute to both reduced processing speed 46 in BD.…”
Section: Hypothesis 1 Alterations In Wm Microstructure a Trait Markermentioning
confidence: 99%
“…Consistent with this interpretation, a number of studies have reported genes to be associated with WMI deficits in BD, including ANK3 and HTLPR . Other studies in BD have found a negative association between length of illness and WMI . We found a trend correlation between the mean AD and duration of illness, but no association with age of onset.…”
Section: Discussionmentioning
confidence: 99%
“…Accelerated aging is commonly observed in several chronic illnesses, increasing the rate of aging-related medical conditions and shortening the life span in patients 1 4 . In particular, bipolar disorder (BD), an often severe and highly disabling psychiatric condition that affects around 1% of the population 5 , has been characterized by many features of aging that can complicate disease outcomes and converge to premature aging (commonly described as “accelerated aging” in the field) 6 , 7 .…”
Section: Introductionmentioning
confidence: 99%